2008
DOI: 10.1007/s00426-008-0154-6
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Stroop task: effect of word arousal and subject anxiety on emotional interference

Abstract: Inconsistent Wndings regarding the emotional Stroop eVect in healthy subjects may be explained by confounding eVects of stimulus valence and arousal, as well as individual diVerences in anxiety. We examined reaction time data in a healthy sample using the emotional Stroop task while carefully matching arousal level of positive and negative words. Independent of valence, emotional relative to neutral words elicited emotional interference, indicating that arousal determines emotional interference. Independent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
116
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(142 citation statements)
references
References 33 publications
16
116
0
10
Order By: Relevance
“…Emotional words seem to more readily attract attention and cause more interference during ongoing tasks, as compared with neutral ones (e.g., Anderson, 2005;Dresler, Mériau, Heekeren, & van der Meer, 2009;Pratto & John, 1991). However, they are more easily remembered and recognized in both immediate (e.g., Hadley & MacKay, 2006;Monnier & Syssau, 2008) and delayed (e.g., Doerksen & Shimamura, 2001;Ferré, 2003) memory tests.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Emotional words seem to more readily attract attention and cause more interference during ongoing tasks, as compared with neutral ones (e.g., Anderson, 2005;Dresler, Mériau, Heekeren, & van der Meer, 2009;Pratto & John, 1991). However, they are more easily remembered and recognized in both immediate (e.g., Hadley & MacKay, 2006;Monnier & Syssau, 2008) and delayed (e.g., Doerksen & Shimamura, 2001;Ferré, 2003) memory tests.…”
Section: Introductionmentioning
confidence: 94%
“…The assessment of each word in each of these three affective dimensions by using the SAM scale is particularly relevant since recent studies have suggested that affective representations of words' intensity (arousal) and their affective content (valence) may rely on distinct cognitive, temporal, and spatial neural substrates (e.g., Dresler et al, 2009;Hinojosa, Carretié, Méndez-Bértolo, Míguez, & Pozo, 2009;Kensinger & Schacter, 2006;Lewis et al, 2007;Mickley & Kensinger, 2008). In particular, valence seems to affect early stages of affective processing (e.g., Kissler et al 2009;Scott et al, 2009;see, however, Hofmann et al, 2009, for early effects of arousal) and to activate neural circuits that are distinct from those associated with arousal: For example, the prefrontal cortex tends to respond to emotional stimuli mainly in a valence-based manner, whereas the amygdala tends to respond in a arousal-based manner (e.g., Kensinger & Schacter, 2006;Lewis et al, 2007;Posner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominent examples are the emotional Stroop (Dresler, Mériau, Heekeren, & van der Meer, 2009;Phaf & Kan, 2007;Thomas, Johnstone, & Gonsalvez, 2007), the recognition memory test (Grider & Malmberg, 2008;Võ et al, 2008;Zimmermann & Kelley, 2010), the lexical decision task (LDT, Kuchinke, Võ, Hofmann, & Jacobs, 2007;Schacht & Sommer, 2009;Scott, O'Donnell, Leuthold, & Sereno, 2009), naming (Estes & Adelman, 2008;Simpson, Snyder, Gusnard, & Raichle, 2001), verb generation (e.g., Simpson et al, 2001), or word-stem completion (Danion, Kauffmann-Muller, Grangé, Zimmermann, & Greth, 1995). However, because numerous variables are known to influence visual word processing (Graf, Nagler, & Jacobs, 2005), well-controlled and reliable emotion-inducing stimulus material is necessary in order to produce interpretable effects.…”
Section: Introductionmentioning
confidence: 99%
“…This approach may be better suited to characterize stimuli for which it is difficult to attribute a primary emotional category (Kanske & Kotz, 2011). Recent studies also suggest that the representations of different affective dimensions rely on distinct cognitive and neural substrates (e.g., Dresler, Mériau, Heekeren, & van der Meer, 2009). For example, whereas the amygdala tends to respond more intensely as a function of stimulus arousal, the prefrontal cortex seems to be more sensitive to the valence of the stimulus (e.g., Kensinger & Schacter, 2006;Lewis, Critchley, Rotshtein, & Dolan, 2007;Posner et al, 2009).…”
mentioning
confidence: 99%